Penerapan Teknologi Tepat Guna Paludikultur Endemik Lokal pada Kelompok Tani Tunas Jaya - Elfis Elfis; Prima Wahyu Titisari; Sepita Ferazona; Syarifah Farradinna; Haliza Nurdilla Nurdilla; Tarjiyo Tarjiyo; Daniel Afrian Hakiki (Asosiasi Dosen Akuntansi Indonesia, 2022)
Paludiculture is one of the agroforestry models to responsible peatland management that preserves ecosystem services while also accumulating carbon. Paludiculture products can provide food, feed, fiber, and fuel, as well as industrial raw materials. The goal of this community service activity is to create canal blocking and applied nucleation demonstration plots to increase the diversity of local endemic paludiculture plant species. The community involved is Kelompok Tani Tunas Jaya (KTTJ) Parit II Village, Sungai Apit District, Siak Regency. The results of the activity in the form of making 2 canal blocking points and 3 demonstration plots of applied nucleation were carried out by KTTJ members. The local endemic paludiculture species planted are Ramin (Gonystylus bancanus), Pulai (Alstonia pneumatophora), Jelutung (Dyera polyphylla), Pinang merah (Areca vestiaria) and Pisang kepok (Musa accuminata). Based on the monitoring and evaluation of activities, members of KTTJ were very satisfied with the implementation of the activities.